Program Wakaf Mushaf sebagai Upaya Mendukung Pendidikan Keagamaan di Desa Garut, Kecamatan Kopo, Kabupaten, Serang, Banten - Siti Hanan; Karismatul Khalifah; Fauji Fauji; Aan Khoirul Anam (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The waqf mushaf program in Garut Village, Kopo District, Serang Regency, Banten, was part of the Student Community Service (KKM) initiative aimed at supporting religious education in the area. This activity arose from the identified need for Qur’anic manuscripts in local institutions, which significantly limited the effectiveness of Qur’anic learning. The program involved several stages: preparation, identifying the needs of the community, fundraising, the distribution of mushaf to madrasahs and Qur’anic centers, and evaluation. A participatory approach was employed, where the community actively participated as both donors and beneficiaries. This approach not only facilitated the smooth execution of the program but also ensured a sense of ownership and responsibility among the local people. The program received strong support, with high levels of community participation in fundraising and distribution activities. The results showed a marked improvement in access to Qur’anic learning, as teachers and students now had better resources to facilitate their study of the Qur'an. The distribution of mushaf not only enhanced the quality of education but also fostered a greater awareness of waqf as an important Islamic social instrument. Through this initiative, the community gained a deeper understanding of the value of waqf in contributing to religious education and promoting social welfare